Role of cis‐zeatin in root responses to phosphate starvation. Issue 1 (26th July 2019) - Silva‐Navas, Javier; Conesa, Carlos M.; Saez, Angela; Navarro‐Neila, Sara; Garcia‐Mina, Jose M.; Zamarreño, Angel M.; Baigorri, Roberto; Swarup, Ranjan; del Pozo, Juan C.
Summary: Phosphate (Pi) is an essential nutrient for all organisms. Roots are underground organs, but the majority of the root biology studies have been done on root systems growing in the presence of light. Root illumination alters the Pi starvation response (PSR) at different intensities. Thus, we have analyzed morphological, transcriptional and physiological responses to Pi starvation in dark‐grown roots. We have identified new genes and pathways regulated by Pi starvation that were not described previously. We also show that Pi‐starved plants increase the cis‐zeatin (cZ) : trans‐zeatin (tZ) ratio. Transcriptomic analyses show that tZ preferentially represses cell cycle and PSR genes, whereas cZ induces genes involved in cell and root hair elongation and differentiation. In fact, cZ‐treated seedlings show longer root system as well as longer root hairs compared with tZ‐treated seedlings, increasing the total absorbing surface. Mutants with low cZ concentrations do not allocate free Pi in roots during Pi starvation. We propose that Pi‐starved plants increase the cZ : tZ ratio to maintain basal cytokinin responses and allocate Pi in the root system to sustain its growth. Therefore, cZ acts as a PSR hormone that stimulates root and root hair elongation to enlarge the root absorbing surface and to increase Pi concentrations in roots.